On the Effect of Environmental Exposure on Dwell Fatigue Performance of a Fine-Grained Nickel-Based Superalloy - Chris Ball (Metallurgical and Materials Transactions A, 2018)
The influence of sulfur contamination on the corrosion-fatigue behavior of a polycrystalline superalloy used in aero-engines is considered. Samples tested under a variety of environmental conditions (including exposures to air, SOx gas, and salt) are characterized through a suite of high-resolution characterization methods, including transmission electron microscopy (TEM), secondary ion mass spectroscopy (nanoSIMS), and atom probe tomography (APT). The primary effect of sulfur contamination is to accelerate the crack growth rate by altering the failure mechanism. The SIMS and TEM analyses indicate Cr-Ti sulfide particle formation at grain boundaries ahead of and around oxidized cracks. The APT analysis suggests that these particles then oxidize as the crack propagates and are enveloped in chromia. The chromia is surrounded by a continuous layer of alumina within the cracks. All of the sulfur detected was confined within the particles, with no elemental segregation found at grain boundaries.